Analysis of Polymorphisms rs7093069-IL-2RA, rs7138803-FAIM2, and rs1748033-PADI4 in the Group of Adolescents With Autoimmune Thyroid Diseases - Sawicka, Beata; Borysewicz-Sańczyk, Hanna; Wawrusiewicz-Kurylonek, Natalia; Aversa, Tommaso; Corica, Domenico; Gościk, Joanna; Krętowski, Adam; Waśniewska, Małgorzata; Bossowski, Artur (Frontiers in Endocrinology, 2020)
Introduction The pathogenesis of autoimmune thyroid diseases is complicated and not completely known. Among the causes of thyroid autoimmunity, we distinguish genetic predisposition and environmental factors. Graves’ disease and Hashimoto’s thyroiditis are associated with a disturbance of immune tolerance of thyroid antigen molecules. The IL2RA gene is located on chromosome 10 and encodes the interleukin 2 receptor (IL2RA), which is expressed by the regulatory T-cells (Tregs) responsible for suppression. It has been shown that this gene and its polymorphism occur in people with various autoimmune diseases (e.g. type 1 diabetes mellitus, rheumatoid arthritis, Graves’ disease, or multiple sclerosis). The FAIM2 gene is located on chromosome 12 and encodes the molecule involved in the apoptosis inhibition process. The PADI4 gene is located on chromosome 1, and its expression is associated with activation of T-cells, differentiation of macrophages, which leads to increased inflammation. Aim The aim of the study was to analyze the polymorphisms of the IL-2RA (rs7093069), FAIM2 (rs7138803) and PADI4 (rs1748033) genes and their correlation to thyroid hormones and anti-thyroid antibodies in pediatric patients with Graves’ disease and Hashimoto’s thyroiditis compared to the control group. Material and Methods The study was performed in 180 patients with GD (mean age 16.5 ± 2), 80 with HT (mean age, 15.2 ± 2.2), and 114 children without any autoimmune diseases (mean age 16.3 ± 3) recruited from the endocrinology outpatient clinic. Three single nucleotide polymorphisms (SNPs): rs7138803-FAIM2, rs7093069-IL-2RA, and rs1748033 PADI4 were determined by TaqMan SNP QuanStudio 12K Flex-OpenArray genotyping with PCR and correlated to thyroid hormones and anti-thyroid antibodies. Results Rs7090369-IL-2RA allele T was more frequent in patients with AITDs (33.7% in GD vs 28.7% in HT, p = 0.077, OR = 1.52) compared with healthy children (25%). Allele T of that gene predisposes to the occurrence of autoimmune thyroid diseases, especially GD and TT genotype gives a statistically significant 5.2 times higher risk of GD (p = 0.03, OR = 5.26) and increased risk of HT (p = 0.109, OR = 4.46). Allele A rs7138803-FAIM2 is more frequent in patients with GD (p = 0.071, OR = 1.45) and HT (p = 0.028, OR = 1.8). In our data the presence of GG genotype of that gene significantly reduces the risk of autoimmune thyroid diseases (p = 0.05, OR = 0.42). Allele C rs1748033PADI4 and its CC genotype were more frequent in patients with autoimmune thyroid diseases, but it was not statistically significant. The occurrence of CT genotype significantly reduces the risk of HT (p = 0.03, OR = 0.4). Conclusions 1). Polymorphisms rs7138803-FAIM2 and rs1748033-PADI4 are more frequent in patients with autoimmune thyroid diseases, more frequent in patients with Hashimoto’ thyroiditis, but the occurrence of GG rs7138803-FAIM2 genotype could reduce the risk of thyrocyte apoptosis inhibition. 2). The TT rs7093069-IL2RA genotype may increase the risk of autoimmune thyroid diseases. 3). Analysis of polymorphisms of given genes in clinical practice will allow to determine predisposition to autoimmune thyroid disease development, to find symptoms of thyroid gland dysfunction earlier and to use appropriate treatment.